Faktor-Faktor Pendukung Partisipasi Perempuan Bekerja pada Sektor Informal di Kota Pekanbaru - Arda, Sakinah Amalia; Budiartiningsih, Rahmita; Utami, Bunga Chintia (Jurnal EMT KITA, 2026)
This study aims to determine what factors support women's participation in the informal sector in Pekanbaru City. The research method used a quantitative approach by distributing questionnaires to 100 respondents selected through quota sampling. Data were analyzed using descriptive analysis. The results show that women's participation in the informal sector in Pekanbaru City is dominated by women aged 45-64 years, have a secondary education level (high school/vocational high school), and are married. Among the factors described, marital status is the most dominant factor in supporting women's participation in the informal sector in Pekanbaru City. The results show that the informal sector functions as an adaptive space for women who face limited access, thus becoming the main support for women's work participation in Pekanbaru City.